Spiritual despots: modern Hinduism and the genealogies of self-rule - Scott, J. Barton (South Asia across the disciplines, 2016)
Introduction: against the priest -- A singular species of despotism -- A popular history of priestcraft in all ages and nations -- Reform affinities -- Guru is God -- Pope-Lila -- Astral ethics -- Conclusion: the circulation of self-rule